1970
DOI: 10.2307/4083704
|View full text |Cite
|
Sign up to set email alerts
|

Pheasant Nesting and Concealment in Hayfields

Abstract: MY associates and I investigated the influence of the quality of nesting vegetation on the sites Ring-necked Pheasants (Phasianus colchicus) selected for their nests on a 36-square-mile tract near Sibley, Ford County, in east-central Illinois. Robertson (1958: 10•18) and Hanson and Labisky (1964) describe the pheasant's environment on the Sibley area. During the years of this study (1957-59), farmers cultivated more than 90 per cent of the land; corn and soybeans were the major crops. Cattle grazed most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Predation is demonstrated to be the principal source of nesting mortality in several Galliform species (Tapper et al 1996, Jimenez & Conover 2001. The nest-site complexity and concealment, depending to a greater extent on physical characteristics at a nest-site, often represent key cues of nest-site selection by ground-nesters (Ricklefs 1969, Hanson 1970. Thus a site that can provide adequate camouflagement from potential predators should be selected for.…”
Section: Discussionmentioning
confidence: 99%
“…Predation is demonstrated to be the principal source of nesting mortality in several Galliform species (Tapper et al 1996, Jimenez & Conover 2001. The nest-site complexity and concealment, depending to a greater extent on physical characteristics at a nest-site, often represent key cues of nest-site selection by ground-nesters (Ricklefs 1969, Hanson 1970. Thus a site that can provide adequate camouflagement from potential predators should be selected for.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation patterns, as well as temperatures, varied widely in 1969, 1970and 1971. During the wet summer of 1969, there were 5 periods when more than 2 inches of rain fell within 3 days (an arbitrary indicator of "excessive" rainfall Pheasant brood counts and spring call counts were made.…”
Section: Discussionmentioning
confidence: 99%
“…Chi-square tests for the null hypothysis that the number of hens observed (all hen observations beginning with the survey when the first brood was seen) in 1971 was no different than the number observed in 1969, did not yield a test value significant at the 0.05 level of probability (P > 0.10). The 1969The -1970 and 1970-1971 differences were not tested since they were of a lesser magnitude than the 5969-1971 difference. Thus, it was concluded that (Freund et 1960:28) With respect to any given brood this is impossible, of course, because after the brood has hatched mortality will cause it to become smaller.…”
Section: Population Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In eastcentral Illinois, oat and hay fields were preferred cover for feeding and roosting (Warner 1979). -Hay meadows and clover were used extensively as brooding areas in Indiana and Iowa (Kozicky 1951, Hanson 1970).…”
Section: List Of Tablesmentioning
confidence: 99%